Behavioral and neurological outcomes of anodal tDCS on stress-impaired working memory - Tan, Rachel Hui Yi (Nanyang Technological University, 2023)
Stress has been found to impair working memory performance. Neurologically, this phenomenon has been associated with a decrease in dorsolateral prefrontal cortex (dlPFC) activity. Anodal transcranial direct current stimulation (a-tDCS) increases cortical excitability, and has been shown to reduce stress-induced working memory impairments when applied over the dlPFC. In the current study, we used fNIRS to investigate the mechanism in which stress-induced working memory impairments are buffered by anodal tDCS. 28 healthy participants were recruited and randomized to receive either anodal or sham tDCS to the right dlPFC. For stress induction, all participants underwent a modified version of the Montreal Imaging Stress Task. Participants’ working memory performance, right dlPFC hemodynamic response and mental fatigue were measured at three time points: baseline, post-stress, and post-tDCS. Additionally, participants’ trait anxiety was measured and used as a covariate in our analyses. Although none of our results achieved significance, we descriptively observed that working memory performance improves post-stress from baseline, and decreases slightly from post-stress to post-tDCS. We also observed right dlPFC oxyhemoglobin hemodynamic response following the same trend as working memory performance. We did not observe much difference in working memory performance between tDCS conditions across timepoints, hence we are unable to conclude that a-tDCS is effective in buffering against stress-induced working memory deficits. We observed that fatigue increases across time, which aligned with our expectations. Lastly, we noted that trait anxiety may not be a useful covariate in influencing working memory performance.